Languages and Compilers for Parallel Computing 24th International Workshop, LCPC 2011, Fort Collins, CO, USA, September 8-10, 2011. Revised Selected Papers - Rajopadhye, Sanjay; Mills Strout, Michelle; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 24th International Workshop on Languages and Compilers for Parallel Computing, LCPC 2011, held in Fort Collins, CO, USA, in September 2011. The 19 revised full papers presented and 19 poster papers were carefully reviewed and selected from 52 submissions. The scope of the workshop spans the theoretical and practical aspects of parallel and high-performance computing, and targets parallel platforms including concurrent, multithreaded, multicore, accelerator, multiprocessor, and cluster systems.
Keywords: Computer science; Computer Communication Networks; Data structures (Computer science).; Electronic data processing; Computer Science; Programming Languages, Compilers, Interpreters; Programming Techniques; Data Structures; Computing Methodologies; Models and Principles; Computer Communication Networks